In-Vitro Screenings for Biological and Antioxidant Activities of Aqueous Extract from Sacha Inchi (Plukenetia volubilis L.) Husks - Thuanthong, Arthittaya; Klomklao, Sappasith; Panyo, Jarurat; Zhang, Yi (Trends in Sciences, 2023)
Industrial processing of the Sacha inchi (Plukenetia volubilis L.) generated a large number of husks, which are one of the major by-products without sufficient utilization. Sacha inchi husk contains rich bioactive compounds unveiling its valorization potential. This study for the first time investigated the biological and antioxidant activities of the Sacha inchi husk extract recovered with distilled water at different temperatures (70, 80, 90 and 100 °C). The results showed that the aqueous extracts from Sacha inchi husks powder obtained at the extraction temperature of 80 °C showed the highest total phenolic content (7.90 mg GAE/g dry extract) and total flavonoid content (5.79 mg CE/g dry extract) and had the highest antioxidant activities (1,055.81, 53.60 and 1.59 µmol TE/g dry extract for DPPH, ABTS and FRAP assays, respectively, and 413.32 µmol EE/g dry extract for metal chelating assay). For antimicrobial activity, all extracts were effective against Gram-positive (Staphylococcus aureus and Listeria monocytogenes) and Gram-negative bacteria (Escherichia coli, Salmonella enteritidis, and Vibrio parahaemolyticus). In addition, Sacha inchi husks powder extraction at 80 °C exhibited the lowest MIC (≤ 0.625 mg/mL) and MBC (≤ 0.625 mg/mL) against all tested microorganisms. The extracts obtained at the extraction temperature of 80 °C also exhibited maximum inhibition of α-amylase (77.71 %) and α-glucosidase (76.40 %). The highest inhibition of tyrosinase activity was presented by the aqueous extract obtained at 80 °C with an IC50 value of 8.40 ± 1.40 mg/mL. Our findings suggested that the aqueous extract of Sacha inchi husks can be served as an economical source of antioxidant, antimicrobial, anti-diabetic and anti-tyrosinase agents. HIGHLIGHTS Sacha inchi husk has relatively high quantities of phenolic compounds The aqueous extracts of Sacha inchi husk showed high antioxidant activity, antimicrobial activity, anti-hypoglycemic activity and anti-tyrosinase activity Sacha inchi husk contains important medicinal values for human health applications GRAPHICAL ABSTRACT